Economic growth and air pollution : cointegration and causality analysis for Malaysia / Zarul Azhar Nasir ... [et al.] - Nasir, Zarul Azhar; CheMohd Rawawi, Mohd Zulkifly; Mohd Sharif, Muhammad Zahidi; Suliman, Nur Aziera (2012)
This paper investigates empirically the causal relationship between economic growth and air pollution in Malaysia over the period 1965 to 2010. To analyze the causal relationship between economic growth and air pollution, the Johansen cointegration test; Vector Error Correction Model (VECM) and Granger causality test are used. The Johansen Cointegration Test results found that these two variables are cointegrated and show the existence of short run and long run relationship. The Granger causality test suggests that there is bidirectional Granger causality among these variables with direction from CO2 to GDP and GDP to CO2.